ANALISIS KOMPETENSI PEDAGOGIK GURU EKONOMI DALAM PELAKSAAN PROSES PEMBELAJARAN DI SMA NEGERI 1 BANDAR PETALANGAN - Fahril, Syahfira; Nurhuda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the pedagogical competence of economics teachers in implementing the learning process at SMA Negeri 1 Bandar Petalangan. The research focused on two main aspects: lesson planning and lesson implementation. This study used a qualitative approach with descriptive methods. Data collection techniques included observation, interviews, and documentation. The research subjects included economics teachers as the primary informant, with students and the vice principal for curriculum as supporting informants. The results showed that the pedagogical competence of economics teachers in the aspect of lesson planning has been systematically developed, but there are still limitations in the variety of methods and use of learning media. In the aspect of learning implementation, teachers have carried out learning activities according to the planned stages, but the learning process is still dominated by conventional methods, resulting in suboptimal student engagement. Furthermore, the use of learning media and technology is still limited, resulting in a lack of variety in material delivery. Based on these findings, it can be concluded that the pedagogical competence of economics teachers in implementing learning at SMA Negeri 1 Bandar Petalangan is not fully optimal, particularly in terms of innovative learning methods and media use. Therefore, efforts are needed to improve pedagogical competence through ongoing training and adequate learning facilities and infrastructure.